IMPLEMENTASI PEMBELAJARAN SAINS DAN PENDIDIKAN AGAMA ISLAM MELALUI METODE KARYA WISATA DALAM MEMAKSIMALKAN KECERDASAN NATURALIS ANAK USIA DINI DI TK ZAVIRA - ILHAM AKBAR; NUR ZAYTUN HASANAH; IKA NUR LATIFAH; INTAN ROUDHOTUS SYARIFAH; BURHAN NUDIN; JANUARIANSYAH ARFAIZAR (Raudhah - Proud To Be Professional, 2021)
Early childhood education is the most important period to form character values. To make it happen, it is necessary to learn using the right method. The field trip method is learning that is done outside of school, where children observe animals, plants, and observe directly and are given the cultivation of Islamic educational values, so that children can understand that everything that is behind the universe there is a Creator, namely Allah SWT. The purpose of this study was to describe the combination of the implementation of science learning and Islamic religious education through the field trip method in order to improve children's naturalist intelligence. The research method used is a qualitative method. Through this research, it was found that the implementation of science learning and Islamic religious education through the field trip method would appear in the thinking process, because children are taught to examine and pay close attention to the universe in order to find Sunnatullah. The procedure for implementing the implementation of science learning and Islamic religious education through the field trip method is through the following stages; first, planning stage, second, learning process, third, learning evaluation. Thus, the combination of implementation in science learning is done by introducing objects, observing objects, so that children can implement them in real life. Learning combined with this field trip method can increase naturalist intelligence so that children become sensitive to the environment and learn to be responsible for the environment and nature and can shape children's character as Khalifatullah fil al-ard.